Strawberry Generation: Keterampilan Orangtua Mendidik Generasi Z - Fikriyah Iftinan Fauzi; Fatin Nadifa Tarigan (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
The current young generation has not been fully able to fulfil the components of the ideal character needed in sustaining the progress and success of a nation in the future. Strawberry Generation represents a beautiful strawberry fruit but is easily fragile and crumbles when stepped on. The birth of the Strawberry Generation is influenced by several factors, including the parenting style of parents in educating and raising their children. Researchers are interested in studying more about the skills of parents in educating today’s children. The use of the phenomenological method as an effort to describe and reveal the skills of parents in educating today’s children and how the behavioural changes that occur as a result of this education are related to the parable of this study, it was found that there are skills of parents in educating children that have the potential to grow them to be part of the strawberry generation, including overprotective parenting, authoritarian parenting, and lack of appreciation and communication. Solutions to minimize children becoming Strawberry Generation include: 1) mental development; 2) give confidence to children to carry out responsibilities that are able to make them learn and upgrade themselves, so that children feel they contribute and feel valuable; 3) attachment between parents and children; 4) train children to make decisions; 5) always understand the condition of the child; 6) instilling a growth mindset. Keywords: Education Skills; Generation-Z; Strawberry Generation